Diagnosis and Psychotherapeutic Needs by Early Maladaptive Schemas in Patients With Inflammatory Bowel Disease - Rada, Cornelia; Gheonea, Dan; Ţieranu, Cristian George; Popa, Denisa Elena (Frontiers in Psychology, 2022)
Inflammatory bowel disease (IBD) is chronic and incurable. Imperious diarrhea, rectal bleeding, fatigue, and weight loss, the main manifestations, cause a decrease in the quality of the patient’s personal and professional life. The objectives of this study were to identify a possible relationship between early maladaptive schemas and disease activity status using logistic regression, to identify the prevalence of early maladaptive schemes in patients and to propose a psychotherapeutic intervention plan. The following were found in a sample of 46 patients aged 16–76 years. An increase in the domain overvigilance and inhibition score had a significant effect (Wald = 6.583, p = 0.010), with an increase of 1.137 CI95% [1.031, 1.254] of the risk of the disease being diagnosed as active. High and very high scores were observed for the emotional deprivation scheme (nearly three-quarters) and dependence/incompetence, vulnerability to harm and illness and subjugation schemas (over 80%). The results show that the proposed model could predict and reconfirm the diagnosis; patients have specific psychotherapeutic needs. The therapeutic goal would be to offer care, empathy and protection, to strengthen self-confidence, to make patients realize that they have the ability to cope, to provide permission, encourage the patient to experiment, and guide the patient to express their anger healthily. The therapy scheme’s intervention could lead to increased long-term disease management capacity and, consequently, reduce costs directly and indirectly caused by this condition.